Lost in the wild : danger and survival in the North Woods - Griffith, Cary J. (Minnesota : Borealis Books, 2006)
"True survival odysseys of two wilderness adventurers who entered the woods in search of tranquility-- but found something else entirely"--Cover p. [4].
Keywords: Wilderness survival -- Minnesota -- Boundary Waters Canoe Area; Search and rescue operations -- Minnesota -- Boundary Waters Canoe Area; Boundary Waters Canoe Area Minn -- Description and travel